Versatile palmyrah palm for prosperity - Vengaiah, PC; Murthy, GN; Sudhagar, IP; Aruna, P; Maheswarappa, HP (Indian Horticulture, 2019)
The palm fibre has great export potential and it is exported to 33 countries with Japan, UK, West Germany, Belgium and Poland accounting to over 80 per cent of export.